2019
DOI: 10.1111/jce.14068
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of combined cryo‐ and radiofrequency‐catheter ablation in patients with supraventricular tachycardias

Abstract: Background There are few data regarding the outcome of a combined cryo‐ and radiofrequency (RF)‐catheter ablation of various types of supraventricular tachycardias (SVTs) originating from near the normal conduction system. METHODS We analyzed all patients undergoing combined cryo‐ and RF‐ catheter ablation at Mayo Clinic, Rochester, MN as part of the ablation of SVTs with potential risks of injury to the normal conduction system. This study aimed to assess the outcome of a combined cryo‐ and RF‐catheter ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…required additional RF ablation to achieve final success, with one failed ablation. 10 By using cryothermal energy only for AVNRT ablation, in a multicenter retrospective study in Japan, Okishige et al reported an overall acute success rate of 99.3% and recurrence rate at 1 year of 3.9%. 11 In 274 children diagnosed as AVNRT, Karacan et al reported F I G U R E 3 Assessment of ablation location in different KT geometry.…”
Section: Discussionmentioning
confidence: 99%
“…required additional RF ablation to achieve final success, with one failed ablation. 10 By using cryothermal energy only for AVNRT ablation, in a multicenter retrospective study in Japan, Okishige et al reported an overall acute success rate of 99.3% and recurrence rate at 1 year of 3.9%. 11 In 274 children diagnosed as AVNRT, Karacan et al reported F I G U R E 3 Assessment of ablation location in different KT geometry.…”
Section: Discussionmentioning
confidence: 99%